Mengkreasikan Entrepreneurship Capital dan Relational Capital UMKM Kuliner di Sentra PKL Surabaya - Agustian Firmansyah; Gendut Sukarno (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
Entrepreneurial capital indicators are talent, courage to take risks, interests, experience, creating change. Indicators of relational capital are trust, taste, customer service, distribution channels. The indicators of entrepreneurial success are conquering challenges, free from all rules, realizing your own ideas, giving other people's work to provide personal satisfaction and benefit others, and the benefits of knowing a lot for career development. The purpose of this study was to determine the effect of entrepreneurial capital & relational capital on entrepreneurial success. This research is a quantitative study with data collection techniques using a questionnaire. While the method of analysis of this research uses Partial Least Square with non-probability sampling through 100 respondents consisting of 52 men and 48 women in several PKL centers in Surabaya. The results of this study concluded: 1) entrepreneurial capital has an effect on entrepreneurial success; and 2) relational capital affects entrepreneurial success.